박인환 시의 불안, 죽음 의식과 이를 통한 시쓰기의 문제 - 박지은(Park, Ji-Eun) (한국시학연구, 2018)
이 연구는 박인환 시에 나타나는 불안과 죽음 의식에 대해 논의한다. 또한 박인환 시에서 나타나는 불안과 죽음 의식이 단순하게 비극적 시대 상황에 처한 지식인의 수동적인 감정이 아니라, 그가 역사를 인식하는 데 보다 근본적인 역할을 하는 중요한 ‘기분’(Stimmung)임을 밝히고자 하였다. 나아가 이 과정을 통해 박인환 시에서 주로 등장하는 모티프들(검은 신, 바람/폭풍, 종말 등)을 해석하고, 박인환 시를 깊이 있게 이해하는 한 지점을 마련하고자 했다. 그의 문학 전반을 관통하고 있는 불안과 죽음 의식은 단순히 한국 전쟁이라는 특정한 원인에 국한되는 것이 아니다. 그의 시에서 불안은 오히려 세계 속에 ‘내던져져 있음’(Geworfenheit)에 의한 존재론적 불안에 가깝다. 그는 이러한 존재론적 불안을 ‘바람’(폭풍)의 이미지로 표현하고 있으며, 그에게 인식되는 무의미의 세계는 ‘검은 신’의 이미지로 나타난다. 존재론적인 불안의 문제는 죽음 의식과도 연관된다. 그는 언제나 자신을 삶과 죽음 사이에 위치한 존재로 위치시키는데, 이 때 그에게 죽음은 곧 닥쳐올 어떤 것이면서 동시에 그로 하여금 현재의 삶을 계속 자각하게 하는 것이다. 그에게 죽음을 인식하는 시간은 자신이 처한 현재를 객관적으로 바라보게 하는 ‘순간’이 된다는 것이 그의 죽음 의식의 특징적인 부분이다. 결국 그가 불안과 죽음 의식을 통해 얻게 된 것은 양심으로서의 시쓰기이다. 화자는 불안 속에서 들려진 양심의 부름을 듣고, 그는 본래적인 자기(시인이 되기)를 회복하려는 노력을 계속한다. 이렇게 봤을 때 불안과 죽음에 대한 인식은 시인이 시쓰기를 계속할 수 있는 동력이 된다. 즉 박인환의 문학에서 ‘불안’은 단순하게 전쟁으로 인한 수동적인 감정을 표현하는 것이 아니며, 오히려 그의 시작(詩作) 전체를 추동시키는 근본적인 요인으로 기능하였다는 것을 알 수 있다. 박인환은 자신의 문학을 통해 특정한 시대를 뛰어 넘는 진정한 실존의 의미에 대해 질문했다. 또한 불안이라는 감정에 잠식되는 것에서 나아가 자신만의 독특한 죽음 의식과 양심의 문제를 보여주었다. This study discusses Park In-hwan’s attitude toward death and anxiety as they appear in his poetry. I argue that the anxiety and consciousness of death that appears in Park’s poetry is not simply the passive emotional response of an intellectual facing a tragic era, but is instead an important mood(stimmung) that serves a more fundamental role in Park’s perception of history. Through this process, I interpret some of the main motifs of Park’s work (the black god, wind/storms, finality, and so on), hoping to provide a perspective from which to understand Park’s poetry with greater depth. The source of the anxiety and consciousness of death that permeates Park’s work is not limited simply to the Korean War. The anxiety of his poetry is instead closer to the ontological anxiety of “having-been-thrown” (geworfenheit) into the world. He expresses this ontological anxiety through the image of ‘wind’ (or storms), and he represents a perceived world of meaninglessness in the image of ‘the black god.’ The issue of ontological anxiety is also linked to his consciousness of death. Park consistently locates himself in the space between life and death, so that to him death is both something fast approaching and, at the same time, the thing that repeatedly makes him aware of life. The discerning feature of this consciousness of death is that the moment the poet perceives death is the moment that forces him to see his present objectively. Ultimately what Park achieves through this consciousness of death is a poetry of conscience. From within his anxiety, the speaker hears the call of conscience, and then makes a continued effort to recover his essential self (to become a poet). In this way, anxiety and perception of death become the motivation for the poet to continue writing poetry. In other words, it can be seen that in Park’s work, anxiety is not only the expression of a passive emotional response to war, but in fact functions as the fundamental element that sets his entire poetic process in motion. Park thereby approaches the question of the real meaning of existence, which extends beyond a specific era, in his literary work. In addition, he moves beyond the encroachments of anxiety as an emotion to reveal a unique attitude towards death and the problem of conscience. KCI Citation Count: 8